Telemedicine solutions for clinical care delivery during COVID-19 pandemic: A scoping review - Ganjali, Raheleh; Jajroudi, Mahdie; Kheirdoust, Azam; Darroudi, Ali; Alnattah, Ashraf (Frontiers in Public Health, 2022)
Background: The unexpected emergence of COVID-19 has changed mindsets about the healthcare system and medicine practice in many fields, forcing physicians to reconsider their approaches to health care provision. It is necessary to add unique, and efficient solutions to traditional methods to overcome this critical challenge. Telemedicine offers a solution to this problem. Remote medical activities could diminish unnecessary visits and provide prompt medical services in a timely manner. Objective: This scoping review aimed to provide a map of the existing evidence on the use of telemedicine during the COVID-19 pandemic by focusing on delineation functions and technologies, analyzing settings, and identifying related outcomes. Methods: This review was conducted following the Arksey and O'Malley framework and the PRISMA-ScR checklist. PubMed and Scopus databases were systematically searched based on specific eligibility criteria. The English publications included in this study focused on telemedicine systems implemented during the COVID-19 pandemic to provide clinical care services. The relevant features of telemedicine systems were summarized and presented into the following four domains and their subcategories, including functionality, technology, context, and outcomes. Results: Out of a total of 1602 retrieved papers, 66 studies met the inclusion criteria. The most common function implemented was counseling, and telemedicine was used for diagnosis in seven studies. Also, in 12 studies, tele-monitoring of patients was performed by phone, designed platforms, social media, Bluetooth, and video calls. Telemedicine systems were predominantly implemented synchronously (50 studies). Also, ten studies used both synchronous and asynchronous technologies. Although most studies were performed in outpatient clinics or centers, three studies implemented a system for hospitalized patients, and four studies applied telemedicine for emergency care. Telemedicine was effective in improving 87.5% of health resource utilization outcomes, 85% of patient outcomes, and 100% of provider outcomes. Conclusions: The benefits of using telemedicine in medical care delivery systems in pandemic conditions have been well documented, especially for outpatient care. It could potentially improve patient, provider, and health care outcomes. This review suggests that telemedicine could support outpatient and emergency care in pandemic situations. However, further studies using interventional methods are required to increase the generalizability of the findings.